2004
DOI: 10.1093/intimm/dxh045
|View full text |Cite
|
Sign up to set email alerts
|

The point mutation of tyrosine 759 of the IL-6 family cytokine receptor gp130 synergizes with HTLV-1 pX in promoting rheumatoid arthritis-like arthritis

Abstract: Rheumatoid arthritis (RA) is a polygenic autoimmune disease. The autoimmunity develops from synergistic actions of genetic and environmental factors. We generated a double-mutant mouse by crossing two murine models of RA, a gp130 mutant knock-in mouse (gp130F759/F759) and an HTLV-1 pX transgenic mouse (pX-Tg), in a C57BL/6 background, which is resistant to arthritis. The mice spontaneously developed severe arthritis with a much earlier onset than the gp130F759/F759 mice and with a much higher incidence than di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 28 publications
2
18
0
Order By: Relevance
“…In other words, dysregulated NF-kB activation in type I collagen + fibroblasts may trigger the feedback loop to increase IL-6 expression in F759 mice, in which IL-6-mediated STAT3 activation is already dysregulated. Consistent with this scenario, we previously showed that transgenic expression of HTLV-1-Tax, which activates NF-kB, enhanced the IL-6-dependent development of arthritis in F759 mice (Ishihara et al, 2004). Moreover, viral IL-17A from herpesvirus saimiri was shown to activate NF-kB and induce IL-6 production in fibroblasts (Yao et al, 1995).…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…In other words, dysregulated NF-kB activation in type I collagen + fibroblasts may trigger the feedback loop to increase IL-6 expression in F759 mice, in which IL-6-mediated STAT3 activation is already dysregulated. Consistent with this scenario, we previously showed that transgenic expression of HTLV-1-Tax, which activates NF-kB, enhanced the IL-6-dependent development of arthritis in F759 mice (Ishihara et al, 2004). Moreover, viral IL-17A from herpesvirus saimiri was shown to activate NF-kB and induce IL-6 production in fibroblasts (Yao et al, 1995).…”
Section: Discussionsupporting
confidence: 61%
“…The F759 mouse line carrying a human version of gp130 (S710L) was established previously (Atsumi et al, 2002;Ishihara et al, 2004;Sawa et al, 2006). IL-6-deficient mice were provided by M. Kopf (Max-Planck-Institute of Immunobiology, Germany), backcrossed with C57BL/6 mice more than 10 times, and crossed with F759 mice.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Excessive activities of arthritogenic cytokines were evoked in IL-1 receptor antagonist knock-out mouse (Horai et al, 2000) lacking a physiological negative feedback molecule, and in gp130F759 with a defective, intracellular negative-regulatory signaling pathway (Atsumi et al, 2002;Ohtani et al, 2000). These wide variety of murine arthritis models with a defined genetic defect will be useful for analyzing the mechanisms for the synergistic action of genetic and environmental factors in RA development (Ishihara et al, 2004), and also the mechanisms for initiation or perpetuation of joint inflammation (Murakami et al, 2011;Ogura et al, 2008). Furthermore, bone marrow transplantation experiment revealed a unique feature of gp130F759 that nonhematopoietic cells with a point mutation Y759F in gp130 are sufficient to induce passive but arthritogenic activation of wild type CD4 + T cells (Sawa et al, 2006).…”
Section: Mouse Models For Ramentioning
confidence: 99%